Paediatric handbook (Wiley-Blackwell, 2009)
* Provides information in an accessible style including clear illustrations. * Includes modern, community-based approaches. * Strong emphasis on the practical management by the doctor at first contact
Keywords: Children -- Diseases -- Handbooks, manuals, etc; MEDICAL -- Pediatrics; Pediatrics; Pediatrics -- Handbooks, manuals; Pediatrics -- Handbooks